1985
DOI: 10.1016/0014-5793(85)80305-7
|View full text |Cite
|
Sign up to set email alerts
|

NAD‐malic enzyme from plants

Abstract: NAD-malic enzyme (NAD-ME) is a primary regulatory enzyme for the metabolism of malate in plant mitochondria. NAD-ME serves an anaplerotic function for the production of pyruvate, and provides CO, for retixation in the Calvin cycle in certain C, and Crassulacean acid metabolism plants. Clues regarding the mechanism of control of NAD-ME in vivo come from numerous studies on the physical and kinetic properties of the enzyme. The kinetics are complex and are altered by the pH of the assay medium as well as by serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…Malic enzymes also can provide reducing equivalents for biosynthetic pathways such as fatty acid biosynthesis (Artus and Edwards, 1985). In addition to their roles as metabolic enzymes, malic enzymes have been recruited in some plants to function in certain specialized processes such as thermogenesis in species of the Araceae (ap Rees et al, 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Malic enzymes also can provide reducing equivalents for biosynthetic pathways such as fatty acid biosynthesis (Artus and Edwards, 1985). In addition to their roles as metabolic enzymes, malic enzymes have been recruited in some plants to function in certain specialized processes such as thermogenesis in species of the Araceae (ap Rees et al, 1983).…”
mentioning
confidence: 99%
“…Vol. 11 2,1996 other plant species, consists of two nonidentical subunits, a and p. The two subunits can function in dimeric, tetrameric, or octameric form, with equivalent numbers of each subunit occurring in each complex (Artus and Edwards, 1985;Wedding, 1989). The two-subunit composition of plant mitochondrial NAD-MEs contrasts with that of a11 other forms of plant, animal, and bacterial malic enzymes, which occur as tetramers of a single subunit.…”
mentioning
confidence: 99%
“…39) Alternatively, malate is oxidized to pyruvate, which is subsequently utilized in the TCA cycle, by NAD þ malic enzyme that exists in plant mitochondria. 40) Furthermore, succinate is provided as a substrate for succinate dehydrogenase in the TCA cycle and a mitochondrial respiratory chain. 39,41) It was also found that the concentration of citrate was extremely low, and no significant difference was observed between the concentrations in thermogenic and post-thermogenic plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes implicated in synthesis and catabolism of this substrate are widely distributed in the cellular compartments. If these enzymes have become well known in herbaceous plants (Macrae, 1971;Davis and Patil, 1975;Wiskich and Dry, 1985;Artus and Edwards, 1985), very few studies have been made on woody plants Cheliak, 1985, 1986;Weimar and Rothe, 1987 (Gerant et al, 1988).…”
Section: Introductionmentioning
confidence: 99%